INNOVATIVE COURSE LECTURE IN CREATIVE ARTS: A PROJECT-BASED LEARNING (PjBL 4.0) ENRICHING 4CS COMPETENCIES - Saragih, Bahagia; Dewi, Nora Ronita; Isdianto, M. Eko (UNIB Press, 2024)
This research is an exploration into the development and impact of innovative teaching materials in the field of Creative Arts, with a particular focus on Project-Based Learning (PBL) as a pedagogical approach that enhances the cultivation of 4Cs competencies: Critical Thinking, Communication, Collaboration, and Creativity among students. This study rigorously adheres to the systematic Research and Development (R&D) model by Borg and Gall, comprising six iterative stages, namely, problem identification, needs assessment, development of materials, and validation by experts, revision, and final product creation. The targeted population for this study consists of 25 students in the 5th semester enrolled in the Creative Arts in ELT course at Universitas Negeri Medan. The research underscores the significance of PjBL as a transformative method to boost student motivation, engagement, and overall academic performance. The comprehensive needs assessment and expert validation demonstrate that the developed materials effectively promote the development of 4Cs competencies. This research goes beyond addressing specific student needs; it also revitalizes the learning journey while nurturing vital 21st-century skills. In essence, it offers a blueprint for effective teaching material development, enriching the educational landscape and meeting the evolving demands of modern education. The results of this study showcase the successful creation of innovative teaching materials that are designed to elevate the students' learning experiences and bolster their 4Cs competencies.